Groundwater pollution containing ammonium, iron and manganese in a riverbank filtration system: Effects of dynamic geochemical conditions and microbial responses. Issue 22 (19th August 2020) - Meng, Li; Zuo, Rui; Brusseau, Mark L.; Wang, Jin‐sheng; Liu, Xin; Du, Can; Zhai, Yuanzheng; Teng, Yanguo
Abstract: Bench‐scale experiments were conducted to investigate the effect of hydraulic loadings and influent concentration on the migration and biotransformation behaviour of three groundwater pollutants: ammonium (NH4 + ), iron (Fe 2+ ) and manganese (Mn 2+ ). Columns packed with aquifer media collected from a riverbank filtration (RBF) site in Harbin City, NE China were introduced synthetic groundwater (SGW) or real groundwater (RGW) were at two different constant flow rates and initial contaminant concentrations to determine the impact of system conditions on the fate of the target pollutants biotransformation. The results showed that the biotransformation rate of Fe 2+ Mn 2+ and NH4 + decreased by 8%, 39% and 15% under high flow rate (50 L d −1 ) compared to low flow rate (25 L d −1 ), which was consistent with the residence‐time effect. While the biotransformation rate of Fe 2+ Mn 2+ and NH4 + decreased by 7%, 14% and 9% under high influent concentration comparing with original groundwater. The 16S rRNA analysis of the aquifer media at different depths after experiments completion demonstrated that the relative abundance of major functional microbes iron‐oxidizing bacteria and manganese‐oxidizing bacteria under higher flow rate and higher influent concentration decreased 13%, 14% and 25%, 24%, respectively, whereas the ammonium‐oxidizing bacteria and nitrite‐oxidizing bacteria exhibited minimal change, compared to the lower flow rate. Above all results indicated that both high flow rate and high concentration inhibit the biotransformation of NH4 +, Fe 2+ and Mn 2+ . The biotransformation of Fe 2+ and Mn 2+ occurs primarily in the 0–40 cm and 20–60 cm depth intervals, respectively, whereas the NH4 + biotransformation appears to occur relatively uniformly throughout the whole 110 cm column. The biotransformation kinetics of NH4 + in RGW and SGW, Mn 2+ in RGW at different depths accords with the first order kinetics model, while Fe 2+ in RGW and SGW, Mn 2+ in SGW presented more complicated biotransformation process. The results should improve understanding of the transport and fate of common groundwater pollutants in RBF and other groundwater recharge environments. Abstract : Bench‐scale experiments were conducted to investigate the effect of hydraulic loadings and influent concentration on biotransformation of three groundwater pollutants, ammonium, iron and manganese. The results showed that the biotransformation of three target pollutants has spatiotemporal characteristics, and both high flow rate and high concentration go against pollutant biotransformation. 16S r RNA demonstrates that functional bacteria distribution was consistent with pollutant biotransformation. The results can improve understanding of the transport and fate of common groundwater pollutants in riverbank filtration environment.